Implications of DPP4 modification of proteins that regulate stem/progenitor and more mature cell types - Ou, Xuan (American Society of Hematology, 2013)
Dipeptidylpeptidase (DPP) 4 has the potential to truncate proteins with a penultimate alanine, proline, or other selective amino acids at the N-terminus. DPP4 truncation of certain chemokines, colony-stimulating factors, and interleukins have recently been linked to regulation of hematopoietic stem/progenitor cells, more mature blood cells, and other cell types. We believe that the potential role of DPP4 in modification of many regulatory proteins, and their subsequent effects on numerous stem/progenitor and other cell-type functions has not been adequately appreciated. This review addresses the potential implications of the modifying effects of DPP4 on a large number of cytokines and other growth-regulating factors with either proven or putative DPP4 truncation sites on hematopoietic cells, and subsequent effects of DPP4-truncated proteins on multiple aspects of steady-state and stressed hematopoiesis, including stem/progenitor cell, and more mature cell, function.